(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Patients in psychiatric care often face complex health issues limiting their ability to engage in physical activity. Pharmacological treatments may further reduce their capacity to exercise. Despite these challenges, physical activity is essential for improving both mental and physical health. Investing in health promotion and disease prevention – specifically by encouraging physical activity in psychiatric care institutions – is crucial for reducing comorbidities and improving patient wellbeing. However, such efforts remain underexposed. This study aims to provide Flemish psychiatric care institutions with a Self-Audit Tool to support developing and implementing a preventive, health-enhancing physical activity policy. Project Description: Development: Drawing on literature and theoretical frameworks on preventive health policy, we developed quality criteria for a physical activity policy. These include (1) criteria assessing concrete actions, and (2) criteria evaluating how physical activity is structurally embedded in the institution. To develop the criteria, we used the 7-stappenplan from the Vlaams Instituut Gezond Leven [Fleming Institute for Healthy Living], a practical model for creating health-promoting policies. This framework guided us in formulating items related to key steps such as setting priorities and objectives, evaluation, and structural embedding. Based on these criteria, we drafted a Self-Audit Tool. Implementation: Several Flemish psychiatric care institutions and experts in physical activity and policy were invited to provide feedback by email or during a live workshop. We asked for input on (1) relevance and (2) feasibility of the questions, (3) clarity of questions and answer options, and (4) completeness of questions, answers, and criteria. Evaluation: Based on feedback, we revised the tool. Experts were given a second opportunity to respond, and their input was incorporated into the final version. Dissemination: In summer 2025, all Flemish psychiatric care institutions (n = 54) will be invited to complete the Self-Audit Tool online, serving as a baseline measurement at the Flemish level for policy actors. Conclusion: We will provide a Self-Audit Tool that supports psychiatric care institutions in reflecting on and improving their physical activity policy. Disseminating the tool as an online questionnaire across Flanders will offer insights into current integration of preventive health promotion and disease prevention and help stimulate further policy development.